2003
DOI: 10.1023/b:ejep.0000036809.30558.8f
|View full text |Cite
|
Sign up to set email alerts
|

Waist Circumference and Testosterone Levels in Community Dwelling Men. The Tromsø Study

Abstract: To examine the relationship of total and free testosterone and sex hormone-binding globulin (SHBG) with central obesity in men, we studied 1548 men aged 25-84 years that took part in the 1994--1995 survey of the Tromsø study. Total testosterone and SHBG were measured by immuno-assay and the free testosterone fraction was calculated. These measurements were analyzed in relation to anthropometric data and lifestyle factors. The age-adjusted correlation between waist circumference (WC) and total testosterone was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
137
4
7

Year Published

2005
2005
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 210 publications
(167 citation statements)
references
References 34 publications
19
137
4
7
Order By: Relevance
“…Higher BMI and waist circumference are associated with lower total, bioavailable or free testosterone and SHBG. 6,7,[144][145][146] The association between higher BMI and lower total testosterone appears more consistent that between BMI and free testosterone. 146,147 Smoking, lower alcohol intake and physical activity or vigorous exercise are factors associated with higher total testosterone and SHBG levels.…”
Section: Testosterone Cardiovascular Risk and Mortality In Aging Menmentioning
confidence: 76%
“…Higher BMI and waist circumference are associated with lower total, bioavailable or free testosterone and SHBG. 6,7,[144][145][146] The association between higher BMI and lower total testosterone appears more consistent that between BMI and free testosterone. 146,147 Smoking, lower alcohol intake and physical activity or vigorous exercise are factors associated with higher total testosterone and SHBG levels.…”
Section: Testosterone Cardiovascular Risk and Mortality In Aging Menmentioning
confidence: 76%
“…In men lower testosterone levels have been associated with obesity, metabolic syndrome and type 2 diabetes mellitus (T2DM) (1)(2)(3)(4)(5). Insulin resistance (IR) linked to visceral adiposity (6) is regarded as a major pathophysiological mechanism leading to the metabolic syndrome and T2DM (7).…”
Section: Introductionmentioning
confidence: 99%
“…[35][36][37] Indeed, PSA expression is under androgen receptor regulation, and obesity and hyperinsulinemia are also associated with lower testosterone levels. [38][39][40][41][42] However, a prior study found no association between leptin or adiponectin and PSA among prostate cancer patients, 43,44 and the component(s) of body adiposity as estimated by BMI that affect PSA levels and perhaps the ability to detect early-stage prostate cancer remain unclear.…”
Section: Introductionmentioning
confidence: 99%